2020
DOI: 10.1002/prop.202000085
|View full text |Cite
|
Sign up to set email alerts
|

Conifold Vacua with Small Flux Superpotential

Abstract: In order to generalize the mechanism of [5] to include conifolds one has to overcome the following obstacle. Introducing fluxes on the conifold cycles generates a conifold superpotential W cf that by itself cannot be tuned to be small. Thus, the total flux superpotential will be small in string units only if the large conifold superpotential is efficiently canceled by a comparably large contribution W bulk generated by fluxes on other cycles, i.e. if 1 See e.g. [37] for an analysis of a de Sitter solution aris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 56 publications
(136 reference statements)
4
110
0
Order By: Relevance
“…In the following we will show that the conditions ( 1)-( 3) above, put a large lower bound for the flux D3-charge, as has been recently observed also in [48]. This large positive D3charge is typically difficult to cancel in a perturbative type IIB setup, even though in our opinion the situation is not as bad as suggested in [21].…”
Section: Bounds On the Flux D3-chargesupporting
confidence: 66%
See 1 more Smart Citation
“…In the following we will show that the conditions ( 1)-( 3) above, put a large lower bound for the flux D3-charge, as has been recently observed also in [48]. This large positive D3charge is typically difficult to cancel in a perturbative type IIB setup, even though in our opinion the situation is not as bad as suggested in [21].…”
Section: Bounds On the Flux D3-chargesupporting
confidence: 66%
“…Recently, explicit mechanisms have been found that can give rise to exponentially small flux superpotentials W0[46][47][48].…”
mentioning
confidence: 99%
“…In general, such an analysis would require a specific treatment which is beyond the reach of the present analysis, as our derivations depend crucially on the universal properties satisfied by the couplings of the EFT at LCS. However, in the specific case of conifold limits of the moduli space, it might be possible to make some progress following an analogous procedure to the one described in [130,131] (see also [132]). In those works, it was explicitly demonstrated that one can stabilise a subset of the complex structure moduli near a conifold point, while fixing the rest near the LCS point, i.e., at a conifold-LCS regime.…”
Section: Jhep04(2021)149mentioning
confidence: 99%
“…Note added : While finishing this work we became aware of an upcoming paper [ 41 ] by Demirtas, Kim, McAllister and Moritz which approaches the same question.…”
Section: Introductionmentioning
confidence: 99%